2018
DOI: 10.1101/383539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesterol interaction sites on the transmembrane domain of the hedgehog signal transducer and Class F G protein-coupled receptor Smoothened

Abstract: Transduction of hedgehog signals across the plasma membrane is a key process during animal development. This is facilitated by the Class F G-protein-coupled-receptor (GPCR) Smoothened (SMO), a major drug target in the treatment of basal cell carcinomas. Recent studies have suggested that SMO is modulated via interactions of its transmembrane (TM) domain with cholesterol. Long time scale (>0.35 ms of simulation time) molecular dynamics simulations of SMO embedded in two different cholesterol containing lipid bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 98 publications
5
29
0
Order By: Relevance
“…S3 ) compared with other lipid species. A locally high radial distribution of GM3 and PIP 2 has been observed previously for simulations of class A receptors ( 28 , 57 ), and PIP 2 binding has been seen during simulations of the class F GPCR Smoothened ( 58 ). Bound PIP 2 molecules have also been seen in a recent cryo-EM structure of neurotensin receptor 1 ( 16 ).…”
Section: Resultssupporting
confidence: 76%
“…S3 ) compared with other lipid species. A locally high radial distribution of GM3 and PIP 2 has been observed previously for simulations of class A receptors ( 28 , 57 ), and PIP 2 binding has been seen during simulations of the class F GPCR Smoothened ( 58 ). Bound PIP 2 molecules have also been seen in a recent cryo-EM structure of neurotensin receptor 1 ( 16 ).…”
Section: Resultssupporting
confidence: 76%
“…The most favourable residues in SMO-CLR complex is TRP109 in the cysteine-rich domain (CRD) of smoothened which contributes the energy with less than −10 kJ/mol. This finding is consistent with a maximal well depth −10 kJ/mol at transmembrane 2/3e, which is the site of cholesterol-binding [8] . Residue TYR394 in SMO-SNG complex contributes to the highest binding energy towards sonidegib with the energy about −3 kJ/mol.…”
Section: Data Descriptionsupporting
confidence: 89%
“…Previous studies revealed that classical Shh pathway components are obviously decreased in the atherosclerotic vasculature (12) and anti-cd31 antibody labeling of Ecs produces Shh immunoreactivity that is not detected in carotid and femoral artery plaques (13). Recently, structural biology studies have focused on the modulated or interaction sites of cholesterol in hedgehog signaling, revealing a direct interaction between cholesterol and Smo, a critical component of the hedgehog signaling cascade, which suggests potential druggable sites (7,(26)(27)(28)(29). LdL is the main carrier of cholesterol, and ox-LdL plays an important role in atherogenesis (30).…”
Section: Discussionmentioning
confidence: 99%